Diversity of understorey residence bird in recently disturbed and regenerated forest in Peninsular Malaysia / Zubaidah Ya’cob - Zubaidah, Ya'cob (2012)
The understanding of the relationship between avian community structure and environmental/ecological change has become the priority for biodiversity conservation processes and predicting the environmental health. Microhabitat change due to logging is one of the components that affects the species composition in the forest understorey. Forest regeneration allows the recovery of understorey bird species to almost as unlogged forest. However, the process generally will take a long period. The aim of this study is to document diversity and composition of understorey bird species inhabiting two forests of about 30 and 50 years after logging. Mist-netting technique was applied in both study areas during twelve visits from January to December 2007. A total of 1423 birds, belonging to 108 species (24 families) were trapped. Of this, 1043 individuals (from 100 species and 24 families) were recorded in the 30 years-old forest and 380 individuals (from 54 species and 15 families) were trapped in the 50 years-old regenerated forest. Species similarity between both regenerated forests was less than 50%. The family Pycnonotidae and Nectariniidae formed considerable proportion (>50%) of total species captured in both areas. Several primary forest babblers such as Short-tailed Babbler (Malacocincla malaccensis) and Black capped Babbler (Pollerneum capistratum) was abundantly caught and had successfully recolonized both forests. This could be due to the presence of undisturbed forest patches that was left untouched during logging activity and the restoration/regeneration process to a well develop canopy and sparse ground cover. Although considered as species that is sensitive to disturbance, several species of woodpeckers were also recorded in both regenerated forests. Some upper strata specialist such as Black and Yellow Broadbill (Eurylaimus ochromalus), Dark throated Oriole (Oriolus xanthonotus) and Crested Jay (Platylophus galericulatus) were captured by mist-nets indicating that the birds were foraging at lower strata, perhaps due to more food resources at lower strata. The presence of 23 nearly threatened species and two vulnerable species (Brown chested Jungle Flycatcher, Rhinomyias brunneata and Blue banded Kingfisher, Alcedo euryzona) in both study areas indicates that the reserves possess valuable resources for survival of critical species even after original forest structure was disturbed by logging activity.